The Abuse of Diplomatic Immunity in the Basfar v Wong Case as Modern Slavery - Rizqi, Miftah Aliya; Utama, Meria; Putri, Cynthia Azhara (Balobe Law Journal, 2025)
Introduction: This research is motivated by the numerous cases of modern slavery committed by diplomatic agent against domestic workers in the residences of diplomats who abuse diplomatic immunity.Purposes of the Research: To analyze the forms and legal consequences of the misuse of diplomatic immunity in the ruling on a case of modern slavery committed by the Saudi Arabian Diplomatic Agent (Mr. Basfar) against a Filipino migrant worker (Ms. Wong) in the United Kingdom.Methods of the Research: This legal research employs a normative legal research method which focuses on international law instruments relating to the issues contained in this study, utilizing statute and case approaches.Results of the Research: The findings indicate that the Saudi Arabian Diplomatic Agent has abused diplomatic immunity by violating the national laws of the United Kingdom as the receiving state, such as regulations concerning minimum wage payments and working hour requirements. The legal consequence for Ms. Wong in this ruling is the right to receive compensation from Mr. Basfar. According to the 1961 Vienna Convention, there are two legal consequences for Mr. Basfar's misuse of diplomatic immunity: the waiver of diplomatic immunity by the sending state and the declaration of a persona non grata sanction by the receiving state.